Compatibility of Metarhizium anisopliae with liposoluble photoprotectants and protective effect evaluation against solar radiation (Bioscience Journal, 2017)
The aim of this study was to analyze the compatibility of the Metarhizium anisopliae JAB 68 isolate with liposoluble photoprotectants and the photoprotection conferred to its conidia. The fungus was cultivated in a medium with the photoprotectants Neo Heliopan® BB, Neo Heliopan® E 1000, Eusolex® 6007 and Neo Heliopan® AV in various concentrations. Vegetative growth, sporulation and germination were assessed to determine compatibility. Then, conidia were suspended in oil containing the compatible photoprotectants, in their respective concentrations, and exposed to 0-7 hours of light from a solar simulator operating at 1,000 W m-2. Neo Heliopan BB® and Neo Heliopan® E 1000were compatible with M. anisopliae at 2% and 1%, respectively. Eusolex® 6007 and Neo Heliopan® AV were compatible up to 8% a 7%, respectively. Conidia exposed to radiation from the solar simulator, with photoprotectant-free oil as its carrier, presented germination of 78.12% after five hours. When adding any photoprotectant to the conidia oily suspension, the germination percentage was always higher than that obtained in the control. Neo Heliopan® BB at 1 and 2% and Neo Heliopan® AV at 0.5% increased the germination. After 7 hours of exposure the germination percentages were 93.77, 94.55 and 98.82%, respectively. Eusolex® 6007 was not as efficient as previous products, but in the same exposure period was able to protect the conidia (88.60% germination) when used at a 1% concentration. Adding photoprotectants in oily formulations of M. anisopliae protects against the harmful effects of UV radiation contributing to the fungus efficiency in the field.